2013
DOI: 10.2485/jhtb.22.375
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intraosseous Odontogenic Carcinoma Arising from a Dentigerous Cyst

Abstract: Malignant tumors arising from dentigerous cysts are classified as primary squamous cell carcinoma derived from an odontogenic cyst or as odontogenic carcinoma according to the 2005 WHO classification and are extremely rare. We report a malignant tumor arising from a dentigerous cyst in the right maxillary anterior teeth , together with a literature review. The patient was a 75-year-old man who visited a hospital with complaining of discomfort in the lingual part of the right maxillary anterior teeth. On panora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Dentigerous cysts occur within the age range of 20–30 years and squamous cell carcinoma arising in dentigerous cysts are often diagnosed in age range of 50–60 years with a mean age of 57 years [ 3 ]. Therefore, we can suggest that PIOC have a relatively slow mode of development, as is observed in the case discussed here.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Dentigerous cysts occur within the age range of 20–30 years and squamous cell carcinoma arising in dentigerous cysts are often diagnosed in age range of 50–60 years with a mean age of 57 years [ 3 ]. Therefore, we can suggest that PIOC have a relatively slow mode of development, as is observed in the case discussed here.…”
Section: Discussionsupporting
confidence: 74%
“…PIOC arising in dentigerous cyst is extremely rare. After cross-checking the last 3 reviews on the subject, only 35 cases have been reported from 1958 to 2015 [ [2] , [3] , [4] ]. In addition two other cases were published in 2017 and 2020 in English literature [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations